Validity and reliability of the situational judgment test instrument for assessing the ‘Pancasila’ student profile - Tri Wahyuni; Wardani Rahayu; Dali Santun Naga (Cogent Education)
Character measurement has become increasingly relevant and needed in recent years due to its significant impact on an individual’s success in various aspects of life. However, existing methods of character measurement such as self-assessment, peer assessment, and observation, still have many limitations. The Situational Judgement Test (SJT) is a behavioral measurement tool with the ability to minimise measurement bias. Therefore, this study aims to demonstrate the content and construct validity of the SJT-based PSP instrument and estimate its reliability. The research findings include an Aiken’s V index of 0.864, loading factor of all variables ≥ 0.5, Goodness of Fit statistics with χ2/df = 122.299/48, CFI = 0.938, TLI = 0.915, RMSEA = 0.066, and SRMR = 0.046, all within the good fit category. The empirical data of PSP align with the GRM model, with item fitness MNSQ method showing 59 items fit to the model. PSP has a Construct Reliability (CR) of 0.967 and an Average Variance Explained (AVE) of 0.830. These findings contribute theoretically and practically to the field of measurement, indicating that the SJT-based instrument is valid and reliable for measuring the PSP.